PENGARUH KEPEMIMPINAN TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI SEBAGAI VARIABEL MEDIASI - Rusady, Kukuh Prasetyo; -, Suprayitno - (Universitas Slamet Riyadi, 2011)
ABSTRACT The purpose of this study was to analyze: (1) the effect of leadership on employee motivation, (2) the effect of leadership on employee performance, (3) the effect of motivation on employee performance, (4) the indirect effect of leadership on the performance of the Civil Service Bureau for Women's Empowerment, Protection children And Family Planning Grobogan through motivation. Sampling with proportional cluster random sampling. The samples used 104 respondents . Data analysis using path analysis . Results showed: (1) leadership significantly influence employee motivation, (2) leadership have a significant effect on the performance of employees, (3) a significant effect of motivation on employee performance, (4) leadership has no direct influence on the performance of the Civil Service Bureau for Women's Empowerment, Child Protection and Family Planning Grobogan through motivation. Keywords : Leadership , Motivation, Performance